მედეას სახის უნივერსალურობისათვის ევრიპიდესთან - გორდეზიანი რისმაგ (ლოგოსი, 2023)
One of the reasons of the popularity of Medea by Euripides is its informativeness. After reading the tragedy, we learn what happened before the events unfolding in the tragedy and what will follow. This presents the play as one logical whole, while the universal character of the motifs (hard to defeat; Medea’s direct relations with Helios and her magic powers; her acute sensitivity toward women’s rights; aversion towards matrimonial breach; untolerance towards defiling the marriage bed; selfless love for her husband; assertion of her own dignity; filicide committed by Medea out of her rage over her husband; split between love for children and the lust for revenge; left without homeland) outlined in this speech, In this speech, formed MEDEA as invalidator of the opposing member (patriarchal overstepping of bounds) of the binary opposition mankind/womankind, as universal protagonist-dramatic figure of womankind, allows for an unlimited number of interpretations.